Competitiveness and ecological impacts of green energy technologies: Firm-level evidence for the DACH region - Spyridon Arvanitis; Michael Peneder; Christian Rammer; Tobias Stucki; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2016)
For a large sample of enterprises in Germany, Austria and Switzerland (the "DACH"region) we study the impact of various policy instruments, such as energy related taxes, subsidies, regulations and standards or negotiated agreements on the firm's ecological and economic performance. To identify the causal linkages, we build a system of twelve equations, tracking first the impacts of policy on the adoption of green energy technologies for distinct areas. In a second set of equations, we estimate the perceived impacts of adoption on the firm's (i) energy efficiency, (ii) carbon emissions and (iii) competitiveness. The results confirm a differentiated pattern of channels for policy to affect the firm's energy efficiency and carbon emissions, while having a neutral impact on its competitiveness.
Keywords: Q48; Q55; O13; O25; O33; 330; Environmental policy; energy policy; technology adoption; innovation; Porter hypothesis